An unexpected coupling–reduction tandem reaction for the synthesis of alkenyl-substituted BODIPYs. Issue 91 (30th October 2019) - Teng, Kun-Xu; Niu, Li-Ya; Li, Jie; Jia, Lu; Yang, Qing-Zheng
Abstract : We report an unexpected coupling–reduction tandem reaction as a general and efficient one-pot synthesis of alkenyl-substituted boron dipyrromethene (BODIPY) from chlorinated-BODIPY and alkyne. Abstract : We report an unexpected coupling–reduction tandem reaction as a general and efficient one-pot synthesis of alkenyl-substituted boron dipyrromethene (BODIPY) from chlorinated-BODIPY and alkyne. This unique synthesis combined the Sonogashira coupling reaction and reduction reaction without adding an additional reagent, which shows higher yields, broader substrate scope and faster reaction rate compared with the conventional methods of the Knoevenagel reaction and Heck coupling reaction.